Consensus and Confrontation in Ibero-American Higher Education Systems [Consenso y Confrontación en Los Sistemas de Educación Superior Iberoamericanos 1 - Mella-Polanco, J (Universidad Nacional Autonoma de Mexico, 2018)
The purpose of this article is to analyze in a comparative perspective the conditions that affect self-regulation and governance of higher education systems (hes) in Latin America. The effects of sectoral state policies on the operation of the dcts will be examined in detail. Within this framework, the authors examine what factors determine consensus or confrontation on higher education systems (hes) in each of the cases studied. Making use of qualitative comparative analysis (qca), 16 cases in the region included in the cinda 2016 report are studied in this article, in which the authors conclude that there are "two worlds" that solve the challenges of self-regulation and governance by different means, that of mass public higher education and that of higher education built on a market logic. © 2018 Instituto Brasileiro de Avaliacao Psicologica. All Rights Reserved.